PENGARUH KELENGKAPAN RESUME MEDIS RAWAT JALAN TERHADAP MUTU REKAM MEDIS DI KLINIK KIMIA FARMA 43 - Rima Rismawati; Irda Sari (INFOKES (Informasi Kesehatan), 2022)
This study aims to determine the effect of the completeness of outpatient medical resumes on the quality of medical records at the Kimia Farma 43 Buah Batu Clinic. The research method used is quantitative with a descriptive approach. Data collection techniques used are by way of questionnaires, observation, and literature review. The sampling technique used saturated sampling technique with a sample of 30 clinical officers. The results of calculations carried out using a questionnaire with a simple linear test model, the number of samples N = 30 and a significant α = 5% obtained tcount = 5.582 and ttable = 1.701 the result is tcount > ttable then H0 is rejected and H1 is accepted, meaning that the completeness of the outpatient medical resume form effect on the quality of medical records at the Kimia Farma Clinic 43 Buah Batu. The effect is 52.7% and 47.3% is influenced by other variables or error . Keywords: Completeness, Outpatient Medical Resume, Quality of Medical Records